COMPENSATION AND WORK ENVIRONMENT ON THE PERFORMANCE OF NON-MEDICAL EMPLOYEES WITH WORK DISCIPLINE AS INTERVENING VARIABLES IN HOSPITAL X BANDUNG CITY - Apriani Kartina; Rina Mutiara; CRI Sajjna Prajna Wekadigunawan (Indonesian Journal of Multidisciplinary Science, 2022)
Hospital X, namely, some employees are still in and out of work, this can be seen from the turnover in the last 3 (three) years and attendance data contained in the HRD section of RS.X.data Turn over for the last 3 (three) years, namely: in 2017 there were 36 employees, in 2018 there were 24 people, and in 2019 there were 30 people. The turnover is very high every year because the average per year is 30% (thirty percent) In this case the researcher wants to highlight three factors that affect employee performance, namely compensation factors, work environment, and work discipline. This selection is based on the fact that these two factors most often appear in theories that discuss the factors that influence employee performance. The purpose of this study was to analyze the effect of compensation and work environment on work quality with performance as an intervening on non-medical employees of RS.X in Bandung. Methods This research uses the type and design of quantitative research, which was conducted on 80 employees. The results of the study that compensation has an influence on work discipline in Non-Medical Employees of Hospital X in Bandung City, the work environment has an influence on work discipline on Non-Medical Employees of Hospital X in Bandung City, compensation has an influence on employee performance on Non-Medical Employees of Hospital X in Bandung. Bandung City, the work environment has an influence on employee performance at Non Medical Employees Hospital X in Bandung City, work discipline has an influence on employee performance at Non Medical Employees Hospital X in Bandung City, compensation has an influence on employee performance with work discipline as a mediating variable (intervening) on ??Non-Medical Employees of Hospital X in Bandung City, and the work environment has an influence on employee performance with work discipline as a mediating variable (intervening) on ??Non-Medical Employees of Hospital X in Bandung City.